Ultra-Sensitive PIN-Photodiode Receiver - Kerstin Schneider-Hornstein; Bernhard Goll; Horst Zimmermann (IEEE Photonics Journal, 2023)
A monolithically integrated receiver consisting of a low-capacitance PIN photodiode and a photo-charge integrating amplifier in 0.18-μm CMOS is introduced launching a new class of ultra-sensitive optical receivers. The integrated PIN photodiode has a junction capacitance of 1.5 fF at a light-sensitive diameter of 30 μm, a responsivity of 0.39 A/W at 635 nm, and rise/fall times of 0.73/0.92 ns at a reverse bias of 20 V. The common-source amplifier integrates the photo-charges on the smallest possible integration capacitor, which is a gate-drain overlap capacitance. The data bits are reconstructed by double sampling. In such a way, the sensitivity of SPAD receivers is achieved, however without using any impact ionization. At 50 Mb/s, a sensitivity of −56.4 dBm for a bit error ratio (BER) of 2 × 10−3 is obtained using a wavelength of 635 nm.